Das neue Gesellschaftsrecht in Japan - Witty, Thomas (Zeitschrift für Japanisches Recht, 2007)
On May 1, 2006, the new Company Code of Japan came into effect. It constitutes the peak of a fundamental overhaul and reform of the Japanese commercial, company, and securities and exchange law and establishes the stock company (kabushiki kaisha) as the central figure of the Japanese company law. At the same time, the new law abolishes the company limited (yûgen kaisha), which played only a minor role in Japanese corporate practice. Along with the reform of the law on stock corporations, other new company types were introduced with the new law, namely the limited liability company (LLC) and the limited liability partnership (LLP). Soon after their introduction, both types have already become popular and play a particular role for the establishment of joint ventures. The major criteria for distinction among the various types of stock corporations available under the new law are the qualifications as private or public company and as large or small company. A stock company, whose shares can only be transferred with the approval of the meeting of the board of directors or the shareholders’ meeting, qualifies as a “private” company, while in a “public” company at least one class of shares has to be freely transferable. A stock corporation is deemed “large” if its paid-in capital is 500 Million Yen ( 3 Million Euro) or more, or if its liabilities amount to 20 Billion Yen ( 130 Million Euro) or more. Other criteria regarding the legal qualification of a stock corporation include the establishment of a board of directors (torishimari yakkai), a board of auditors (kansa yakkai), and the adoption of the Anglo-Saxon one-tier committee-type organization (i’inkai setchi kaisha), which was already introduced in Japan in 2003. Further significant changes concerning stock corporations include the abolishment of the statutory minimum paidin capital [10 Million Yen ( 75,000 Euro) under the old law and the option to appoint only one executive director (torishimari-yaku) to the management of the company. The various alternatives of how to structure a stock corporation under the new law and the use of this and other newly introduced company types in practice are illustrated in some practical examples.